SURVEY PERILAKU PENANGGULANGAN UPAYA PENCEGAHAN COVID-19 PADA TATANAN KELUARGA PADA MAHASISWA KEPERAWATAN DAN KEBIDANAN - Elisabeth Surbakti; Dame Evalina Simangunsong; Nurlina Tarigan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Corona virus (SARS-cov-2), is a disease called Coronavirus disease 2019 (Covid-19). The behavior of the community towards the prevention of Covid-19 is still low, which is thought to play a role in the increase in cases from time to time. The role of the community is urgently needed to suppress the transmission of Covid-19. The general public, in this case the D-three students of Midwifery and Nursing at the Medan Ministry of Health Poltekkes, need to disseminate information on the transmission of Covid-19. Surveys on student behavior can play a role in socializing the prevention of Covid-19 transmission. This study aims to determine the description of student behavior towards the prevention of Covid-19 transmission in the family setting. The research method with a survey, identifies the characteristics of the D-three Nursing and Midwifery students and their behavior (knowledge, attitudes and actions) towards the prevention of Covid-19 in the family setting. Data collection from March to May 2020. The population is D-three students in Midwifery and Nursing with a total of 595 respondents. The research procedure was carried out by collecting data through google forms such as student characteristics (gender, age, ethnicity, place of residence, level/class), behavior (knowledge, attitudes and actions) regarding overcoming Covid-19 prevention efforts in the family setting. The results of the study: 97.6% of the information regarding the prevention of Covid-19 transmission, the general source of information was through social media, 85.8%, 68.1% of respondents with good knowledge, 79.4% strongly agree, do prevention 68.9%, and in the family setting the attitude of the family strongly agrees 69.6%. There needs to be further learning for students about infectious disease pandemics in the community, especially the prevention of Covid-19 transmission in the family and community settings.